Descentralização, regulação e desenvolvimento econômico local - Lima, João Marcelo da Costa e Silva (2016)
The purpose of this dissertation is to investigate the consequences of the recentralization process Brazil has been gradually experiencing on (i) the effectiveness of local regulation issued by large local governments (those to which the assumption of inability of generating wealth and managing local affairs may not apply); and, more broadly, (ii) on the capacity of large local governments to carry out local regulation. In the past, the following benefits have been attributed to decentralization: (i) it can raise the quality of local services and policies; (ii) it can promote economic development; and, particularly, (iii) it can strengthen democracy by allowing citizens to have more access to the local authorities in charge of many of the affairs that affect them daily. Of the three alleged benefits, the one that best survives scrutiny from the literature is the third one, which is why the recentralization process Brazil has been experiencing may be problematic to the extent that this benefit is compromised. The hypothesis of this dissertation is that the recentralization process compromises the strengthening of democracy at a local level, as it: (i) reduces the local autonomy necessary for local governments to carry out local regulation policies that respond to the preferences of the local population; and (ii) creates obstacles for the local population to know which federative body (the central government, states or local governments) is responsible for many of the local affairs that cities must handle. I argue that this compromises the effectiveness of local regulation aimed, explicitly or not, at fostering local economic development and, more broadly speaking, that this reduces the capacity of local governments to implement local regulation, for three main reasons: (i) it allows for unarticulated, excessive and state intervention in cities, implemented by federative entities that are not necessarily aligned, and which therefore may act in a conflicting manner; (ii) it encourages a 'blame-shifting' game between federative entities, as one can 'pass on' responsibility to the other, or share it; (iii) it makes it more difficult for local regulation to be the result of the local population’s preferences. This diagnosis of local governments’ weak institutional performance leads one to question whether it would be desirable for institutional reforms aimed at making the governments of large cities more responsive to the local population and being in a better position (as well as having more incentives) to implement local regulation polices that indeed have the possibility of fostering local economic development.